SOME RELIABILITY ESTIMATES FOR GENERALIZED EXPONENTIAL DISTRIBUTION WITH PRESENCE OF k-OUTLIERS - Mahmoudi, Seyed Mahdi; Zarei, Reza (Revstat, 2022)
* This paper studies the problem of parameters estimation for the two-parameter generalized exponential distribution in presence of outliers to estimate the reliability (R) as a measure of system performance. The maximum likelihood and Bayes estimators of R are obtained when the scale parameter [lambda] is known and unknown. Monte Carlo simulations and bootstrap approach are performed to compare the different proposed methods. Keywords: * Bayes estimator; bootstrap method; generalized exponential distribution; maximum likelihood estimator; Monte Carlo simulation; outliers. AMS Subject Classification: * 49A05, 78B26.